140 years of medical physics in Romania. (February 2021) - Bodale, Marin; Marcu, Loredana G.
Graphical abstract: Highlights: Medical physics teaching in Romania in dated back to 1880. Despite the long history of teaching and training, several challenges are still persisting. Medical physicists have various educational backgrounds affecting the system's balance. There is no national registration scheme in place for medical physicists. We aim to setup a board of experts for national examination of medical physicists. Abstract: In 2020 the Romanian College of Medical Physicists celebrated 140 years of medical physics in Romania. The article presents a short historical perspective of medical physics teaching and education in the country, focusing on the current situation and challenges that we are facing in regards to staffing, training and accreditation. While certain aspects concerning the procurement of radiotherapy / medical imaging devices and staffing are improving over the years, others, related to clinical training and education, as well as the national recognition of the profession continue to pose a challenge.